Landing Preference and Reproduction of Rhopalosiphum padi (Hemiptera: Aphididae) in the Laboratory on Three Maize, Potato, and Wheat Cultivars. Issue 1 (27th May 2015) - Schröder, Michelle L.; Glinwood, Robert; Ignell, Rickard; Krüger, Kerstin
Abstract : The bird cherry—oat aphid Rhopalosiphum padi (L.) transmits the nonpersistent Potato virus Y (PVY) to seed potatoes. Planting a nonvirus host plant around the main crop can reduce PVY incidence, because aphids tend to land in high numbers at the edge of a field and the crop border acts as a virus sink. This study determined R. padi landing and settling preferences and reproductive rates on three cultivars each of maize and wheat compared with potato in the laboratory as a basis for identifying an attractive crop border plant. Aphids were reared on maize and wheat to control for bias due to previous experience. Irrespective of origin, alates preferred to land almost exclusively on maize and wheat rather than on potato cultivars in choice experiments. Aphid settling on the maize and wheat cultivars depended on aphid origin. In no-choice experiments, R. padi produced the highest number of offspring on the wheat cultivars, irrespective of origin. Plant nitrogen content and trichome density did not influence R. padi reproduction. The study demonstrates that host plant preference of aphids may vary between plant cultivars and can therefore influence the effectiveness of a crop border. The high landing rate but low reproduction suggest that maize cultivars '6Q-121' and '78-15B' could be suitable crop border plants in regions where R. padi is abundant. Before testing potential crop border plants in the field, cultivars should be screened using aphid landing, settling and reproduction as selection criteria.